Glycolysis Inhibition Induces Functional and Metabolic Exhaustion of CD4+ T Cells in Type 1 Diabetes - Martins, Christina P.; New, Lee A.; O’Connor, Erin C.; Previte, Dana M.; Cargill, Kasey R.; Tse, Isabelle L.; Sims- Lucas, Sunder; Piganelli, Jon D. (Frontiers in Immunology, 2021)
In Type 1 Diabetes (T1D), CD4+ T cells initiate autoimmune attack of pancreatic islet β cells. Importantly, bioenergetic programs dictate T cell function, with specific pathways required for progression through the T cell lifecycle. During activation, CD4+ T cells undergo metabolic reprogramming to the less efficient aerobic glycolysis, similarly to highly proliferative cancer cells. In an effort to limit tumor growth in cancer, use of glycolytic inhibitors have been successfully employed in preclinical and clinical studies. This strategy has also been utilized to suppress T cell responses in autoimmune diseases like Systemic Lupus Erythematosus (SLE), Multiple Sclerosis (MS), and Rheumatoid Arthritis (RA). However, modulating T cell metabolism in the context of T1D has remained an understudied therapeutic opportunity. In this study, we utilized the small molecule PFK15, a competitive inhibitor of the rate limiting glycolysis enzyme 6-phosphofructo-2-kinase/fructose-2,6- biphosphatase 3 (PFKFB3). Our results confirmed PFK15 inhibited glycolysis utilization by diabetogenic CD4+ T cells and reduced T cell responses to β cell antigen in vitro. In an adoptive transfer model of T1D, PFK15 treatment delayed diabetes onset, with 57% of animals remaining euglycemic at the end of the study period. Protection was due to induction of a hyporesponsive T cell phenotype, characterized by increased and sustained expression of the checkpoint molecules PD-1 and LAG-3 and downstream functional and metabolic exhaustion. Glycolysis inhibition terminally exhausted diabetogenic CD4+ T cells, which was irreversible through restimulation or checkpoint blockade in vitro and in vivo. In sum, our results demonstrate a novel therapeutic strategy to control aberrant T cell responses by exploiting the metabolic reprogramming of these cells during T1D. Moreover, the data presented here highlight a key role for nutrient availability in fueling T cell function and has implications in our understanding of T cell biology in chronic infection, cancer, and autoimmunity.